2016
DOI: 10.2522/ptj.20150526
|View full text |Cite
|
Sign up to set email alerts
|

Role of Physical Therapists in Reducing Hospital Readmissions: Optimizing Outcomes for Older Adults During Care Transitions From Hospital to Community

Abstract: Hospital readmissions in older adult populations are an emerging quality indicator for acute care hospitals. Recent evidence has linked functional decline during and after hospitalization with an elevated risk of hospital readmission. However, models of care that have been developed to reduce hospital readmission rates do not adequately address functional deficits. Physical therapists, as experts in optimizing physical function, have a strong opportunity to contribute meaningfully to care transition models and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
76
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 61 publications
3
76
0
5
Order By: Relevance
“…Delaying or deferring home-or community-based physical therapy for patients at high risk for hospitalization secondary to new disability may cause substantial harm. 13,14 Physical therapists also perform other tasks-such as home safety assessments, acquisition of important durable medical equipment, and caregiver training-that cannot always be delayed without risking functional decline and a concomitant risk for hospitalization. Indeed, patients who experience a decline in physical function after hospital discharge have a 250% increase in risk for hospital readmission or death.…”
Section: Reducing Risk For Avoidable Hospitalizationmentioning
confidence: 99%
“…Delaying or deferring home-or community-based physical therapy for patients at high risk for hospitalization secondary to new disability may cause substantial harm. 13,14 Physical therapists also perform other tasks-such as home safety assessments, acquisition of important durable medical equipment, and caregiver training-that cannot always be delayed without risking functional decline and a concomitant risk for hospitalization. Indeed, patients who experience a decline in physical function after hospital discharge have a 250% increase in risk for hospital readmission or death.…”
Section: Reducing Risk For Avoidable Hospitalizationmentioning
confidence: 99%
“…Furthermore, because functional impairment increases the risk for hospital readmission in patients with HF, 36 physical therapists also likely have a central role in effective post-acute HHC. 37 In 1 pre-post study of a program that coordinated nurse and physical therapist home visits for patients discharged with HF, researchers found a 16% absolute reduction in hospital readmissions during the HHC episode of care. 38 …”
Section: More Evidence Needed: Hhc For Patients With Hfmentioning
confidence: 99%
“…2 Most older adults who experience ADL loss are unlikely to recover independence in ADLs, even as their medical illnesses resolve; at 1 year, it has been reported that only 28% have fully regained function, and 41% have died. 1,3,4 Furthermore, older adults with functional deficits have higher rates of hospitalization and recurrent readmissions, 5 along with higher overall healthcare use and costs. 6,7 Medicare recipients accounted for nearly half of all hospital spending in 2012.…”
mentioning
confidence: 99%